Food neophobia and intervention of university students in China - Hua Tian (Wiley, 2021)
Abstract Background Food neophobia was defined as the unwillingness or avoidance to eat new foods. There are many studies on food neophobia in children, but few in university students. This study was to examine the level of food neophobia of Chinese university students. The aim is to find a way to help them relieve food neophobia. Methods A total of 2,366 university students (16–22 years old) from Xinyang normal university were recruited to conduct a questionnaire survey on food neophobia scale (FNS) of Chinese version, which contained 10 questions. Significant difference analysis and principal component analysis were conducted. Results For Chinese university students, willingness to try new food, trust in new food, eating disorder, and food pickiness were the characteristic indexes to evaluate the food neophobia. Gender had no significant effect, but long‐term nutrition courses had a great impact on food neophobia of university students. Conclusions The level of food neophobia of Chinese university students is relatively high. To formulate and implement a continuous diet and nutrition education plan is good and necessary to relieve the food neophobia. Implications for Practice These data complement the limited literature on food neophobia of university students, which will help to develop intervention plans to reduce eating disorders and support the need for further research to reveal the potential mechanism.